ANALYSIS OF THE EFFECT OF ORGANIZATIONAL COMMITMENT, ORGANIZATIONAL CLIMATE AND ORGANIZATIONAL CULTURE ON THE PERFORMANCE OF SUNGAI PENUH CITY FIRE AND RESCUE SERVICE EMPLOYEES - Suhelmi Helia; Salmi Salmi; Ropi Depian Wandri; Roni Maiwadri; Darmendra Darmendra (SEAN Institute, 2022)
This study aims to see the effect of (1) Organizational commitment to the Performance of Sungai Penuh City Fire and Rescue Service Employees. (2) Organizational climate to Sungai Penuh City Fire and Rescue Service Employee Performance. (3) Organizational culture towards the Performance of Sungai Penuh City Fire and Rescue Service Employees. (4) The organization's commitment, organizational climate and organizational culture are mutually impactedon the performance of the Sungai Penuh City Fire and Rescue Service employees. The population in this study was 31 employees of the Sungai Penuh City Fire and Rescue Service. And the technique of determining the sample taken as a respondent with this sampling technique using the total sampling technique (overall sample) total sampling is a sampling technique where the number of samples is equal to the population (Sugiyono, 2017). The reason for taking the total sampling is because according to (Sugiyono, 2017) the total population that is less than 100 the entire population is used as a research sample all. The results of this study show that (1) The organization's commitment has a positive influence on the work of employees in the Sungai Penuh City Fire and Rescue Service. (2) The organizational climate has a positive influence on the performance of employees of the Sungai Penuh City Fire and Rescue Service. (3) The organizational culture providesa positive impact on the performance of the employees of the Sungai Penuh City Fire and Rescue Service. (4) Organizational commitment, organizational climate and organizational culture together have a significant effect on the performance of employees of the Sungai Penuh City Fire and Rescue Service.